WHERE THE EUROPEAN UNION SHOULD MULTIPLY ITS MONEY: STIMULATING MEASURES IN THE ECONOMIC MONETARY UNION - Groeneveld, Anouschka; Heijman, Wim (Economics of Agriculture, 2013)
The aim of this article is to investigate in which sectors and countries the European Union should invest to diminish the economic gap between different member states. It answers the question at which sectors and regions the European regional policy should be directed. In an attempt to indicate which regions and sectors have favorable investment opportunities, multipliers are calculated for all but three countries of the Economic Monetary Union. The multipliers are calculated using a technique described by Jensen et al. (1979) and Heijman and Schipper (2010). The highest multipliers are found within the Construction sector. To provide policy recommendations we focus on countries with high multiplier values and high unemployment rates. If we assume that multiplier values and unemployment rates are important, then the European Union should spend most in Slovakia, Estonia, Italy, Greece, and Spain. The spendings in Estonia, Slovakia, and Greece would fall under the Cohesion Funds.